PERLINDUNGAN HUKUM TERHADAP TKI OLEH PEMERINTAH INDONESIA DALAM PERSPEKTIF SIYASAH DAULIYAH (STUDI KASUS PEMBUNUHAN NURUL AIDAH TKI ASAL BATUBARA SUMATERA UTARA DI MALAYSIA) - Iis Erika Faradila; Arifuddin Muda Harahap (UNES Law Review, 2023)
The increasing growth rate of the workforce in Indonesia is not matched by the provision of jobs by the Indonesian government, resulting in job seekers requiring them to look for work abroad. Therefore, many problems arise that require the Indonesian government to make policies in providing legal protection too workers who get into trouble into trouble when working abroad. The purpose of this study was to find out the Indonesian government’s efforts to provide legal protection for Indonesian workers and find out the siyasah dauliyah review in viewing government policies in providing legal protection for Indonesian workers. This research shows that the Indonesian government has made efforts to provide legal protection to Indonesian workers by making several policies and in accordance with the basics of siyasah dauliyah, one of which is cooperation and deliberation.